Synthesis, Characterization and Thermal Studies of Ru(III), Rh(III) and Pd(II) Complexes Derived from 2-Hydroxy-1-Naphthaldehyde and 3-Amino Phenol - Chavan, V.L.; Mehta, B.H. (Asian Journal of Chemistry, 2010)
The Schiff base derived from 2-hydroxy-1-naphthaldehyde and 3-amino phenol and its metal complexes have been synthesized and characterized by IR, 1H NMR, UV, elemental analysis, molar conductivity and thermal analysis. From the analytical and spectral data, the stoichiometries have been found to be 1:2 for all the complexes. The Ru(III) and Rh(III) complexes exhibit octahedral structures, whereas Pd(II) complex show square planar structure.